ECOLOGY AND FISHERY STATUS OF UKAI RESERVOIR, GUJARAT - BHAKTA, DIBAKAR; RAO, D. S.K. (Journal of the Inland Fisheries Society of India, 2021)
The study dealt with the ecology and fish diversity of Ukai reservoir, Gujarat, which was undertaken during July 2014 to August 2015. During the study 50 fish species belonging to 9 orders, 17 families and 38 genera were recorded. The order Cypriniformes was dominant with 22 species followed by Siluriformes with 12 species. The most abundant species in the reservoir were Catla catla, Labeo rohita, Cirrhinus mrigala, Labeo calbasu, Wallago attu, Sperata aor, Systomus sarana, Clupisoma garua, Macrobrachium rosenbergii and Ompok bimaculatus. A total 34 lakh fingerlings of Indian major carps namely catla, rohu and mrigal were stocked in the reservoir during 2013-14, which reflects in the production trend. Fish production data (2014-15) of the reservoir showed that carps contributed 50.68% of the total production followed by catfishes 10.04%, murrels 3.0%, eels 2.86 and others 33.43% with productivity of the reservoir at 279 kg ha -1. Species like Tenualosa ilisha, Tor tor, S. seenghala, S. aor, Labeo fimbriatus and W. attu gradually decreased over the years after impoundment. The study indicated that Ukai reservoir is rich in fish diversity Regular stocking, fishing ban during breeding season, etc. would sustain the fish diversity of the reservoir.Key words: Ecology, fish diversity, Ukai reservoir, management measures, Gujarat